ANALYSIS OF CASSAVA TUBER MARKETING IN RURAL AND URBAN MARKETS IN EDO SOUTH AGRO-ECOLOGICAL ZONE, EDO STATE, NIGERIA (American International Journal of Agricultural Studies, 2023)
Cassava farmers and marketers are faced with problems bothering on poor pricing of the product locally, with attendant negative implications on their profitability. Hence, this study focused on the profitability of cassava marketing in rural and urban markets in Edo South Agro-Ecological Zone, Edo State, Nigeria. A three-stage sampling procedure was used in drawing up a sample of 161 cassava marketers from seven purposely selected major cassava markets. Data collected with the aid of a well-structured questionnaire were analyzed using descriptive statistics, budgetary analysis and regression analysis. Cassava tuber marketing was shown to be profitable in the study area with a monthly gross margin of ₦29,061.4 and a return per Naira invested of 0.29 (29%) for rural marketers. Urban marketers had a mean monthly gross margin of  ₦19, 961.3 per marketer and a return per Naira invested of 0.32 (32%). Rural markets were found to be more efficient (576.78%) than urban markets (168.84%). The major factor militating against the farmers and marketers in their adopted management practices was having little money to spend. It is concluded that in order to improve the profitability of cassava tuber marketers in the study area, measures should be taken to cut down on the cost of transportation.JEL Classification Codes: Q17.